2021
DOI: 10.1108/jbim-10-2020-0451
|View full text |Cite
|
Sign up to set email alerts
|

Organizing sports events: the promoters’ perspective

Abstract: Purpose This study aims to develop a battery of items that assess the factors affecting sports events’ success from the promoters’ perspective and a measurement tool that identifies these stakeholders’ main priorities based on the importance-performance analysis (IPA) framework. Design/methodology/approach The research was conducted using mixed methods. In the first qualitative step, sports event management’s main dimensions were identified based on the existing literature and a comprehensive battery of corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…The literature [9] explored the changing functions of modern sports and suggested that the psychological, physical, social, and cultural functions in modern sports are gradually becoming a commercial need to satisfy the growth of monopoly capital. Although China's sports business has developed late, it has involved an excessive deal of consideration from numerous scholars in sports and economics, and extensive research has been conducted on the connotation, policy effects, and regional attractiveness of the sports business [10]- [12]. The literature [13] analyzed the current situation and connotation of the competitiveness of China's sports business and discussed the factors affecting the competitiveness of China's sports business based on the "diamond model".…”
Section: Introductionmentioning
confidence: 99%
“…The literature [9] explored the changing functions of modern sports and suggested that the psychological, physical, social, and cultural functions in modern sports are gradually becoming a commercial need to satisfy the growth of monopoly capital. Although China's sports business has developed late, it has involved an excessive deal of consideration from numerous scholars in sports and economics, and extensive research has been conducted on the connotation, policy effects, and regional attractiveness of the sports business [10]- [12]. The literature [13] analyzed the current situation and connotation of the competitiveness of China's sports business and discussed the factors affecting the competitiveness of China's sports business based on the "diamond model".…”
Section: Introductionmentioning
confidence: 99%